Monster truck drag racing - Hintz, Martin; Hintz, Kate (Mankato, Minn. : Capstone Press, 1996)
Describes the various kinds of monster truck drag races and the vehicles involved; includes a history.
Includes bibliographical references (p. 43) and index.
Keywords: Truck racing -- Juvenile literature; Monster trucks -- Juvenile literature; Drag racing -- Juvenile literature; Truck racing; Monster trucks; Drag racing